Rectal cancer and chemoradiation in Iraq: systematic review and meta-analysis - Alshewered,Ahmed Salih (2019)
Abstract Background Rectal cancer is one of the most common malignant tumors of gastrointestinal tract. Combining chemotherapy with radiotherapy has a sound effect on its management. Objectives Assessment the patterns of characterizations of rectal cancer. Evaluation of the efficacy, and long-term survival of pre-/ postoperative chemoradiation. Collecting all eligible evidence articles and summarize the results. Methods By this systematic review and meta-analysis study, we include data of chemoradiation of rectal cancer articles from 2015 until 2019. The research was carried out at Baghdad Medical City oncology centers. Accordance with the PRISMA guidelines, and the Newcastle-Ottawa Scale used. Results Starting with gender distribution as M:F ratio of 0.94:1.06. Regarding the age, recorded mean ± SD of 48.7 ± 14.2 years. Rectosigmoid represented the most common site as 50(49.5%), and adenocarcinoma was common histopathology as 76(75.2%) of patients, with localized stage in 50(49.5%). The moderate differentiation was most grade as 65(64.4%). The distant from anal verge mostly seen was 5-10 cm in 59(58.4%). The pulmonary was commonest site of metastasis in 11(10.9%). Most patients undergo APR operation, which has done in 41(40.6%). Adjuvant chemoradiation received by 40(39.6%) patients, whereas neoadjuvant chemoradiation gave to 25 patients. A total of 2609 articles from 12 databases met our search strategies. The highest Newcastle-Ottawa score (8) demonstrated in three studies, and median score (7) calculated in five studies. Conclusions The incidence belonged to 5th and 6th decade of life. Rectosigmoid represented the most common site. Mostly, the 5-10 cm distant of tumor from anal verge was common finding. The pulmonary was most site of metastasis. We concluded the formulation of a novel point that survival benefit found in many pre or postoperative chemoradiation trials in rectal cancer.